Description of The Risk Level of Heart Disease to The Ratio of LDL/HDL Patients at Rsud Dr. Adjidarmo - Venny Patricia; Nining Kurniati; Citra Trisna; Nana Munawar (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
The increased risk of stroke is associated with high low-density lipoprotein (LDL) cholesterol, low high-density lipoprotein (HDL) cholesterol, and a high ratio of LDL and HDL cholesterol, and will be amplified if other stroke risk factors are present. The purpose of this study was to determine the ratio of LDL and HDL cholesterol in patients at RSUD Dr. Adjidarmo. The research design is descriptive research. With a total population of 150 people, a sample of 20% of the population, namely 30 people, was taken. The data collection technique in this study was primary data, namely through the medical records of heart patients who had received outpatient care at the Cardiac and Vascular Polyclinic at RSUD Dr. Adjidarmo Rangkasbitung. The data analysis technique was performed by entering data into tables and calculating the ratio between LDL and HDL for the group of patients at risk of heart disease based on the ratio obtained. The results of the study of the 30 respondents who were examined gave an overview of the results of the examination, with low risk LDL/HDL ratio values (low risk) of 21 people (70%); the average risk LDL/HDL ratio was 5 people (16.67%); the moderate risk LDL/HDL ratio was 1 person (3.3%); and the high risk LDL/HDL ratio was 3 people (10%). Patients who have a risk of developing coronary heart disease are 16 men (53.3%) and 14 women (46.7%). The average age of patients with coronary heart disease is over 50 in men and over 39 in women.